Notational analysis of sprint kayaking: Differentiating between ability levels - Brown, M. B.; Lauder, M.; Dyson, R. (International Journal of Performance Analysis in Sport, 2011)
Sprint kayaking involves simultaneously balancing the boat and maintaining peak kayak velocity. Previous investigation focused on the technique and performance of elite competitors, however little research has compared elite and sub-elite paddlers. This study aimed to determine, using notational analysis, whether key technique factors could be identified which would provide insight for lower ability paddlers seeking to develop their paddling technique. 135 kayak paddlers (78 International; 38 national and 19 club) were recorded competing over 200 m and 500 m. For both distances higher stroke rates, shorter stroke times, and shorter glide times were indicative of elite paddlers for both men and women (P < 0.017). Using a 0 - 5 ranking scale for 22 spatial body and boat variables revealed significantly greater stroke width, forward reach, trunk rotation and leg motion in the elite (P < 0.017), indicating that amateur paddlers should incorporate greater use of the musculature in the legs and trunk to improve kayak velocity and performance.